Equivalent circuit modeling of two-port Al-doped Zinc Oxide CMOS SAW resonator using MATLAB™ - Md Ralib @ Md Raghib, Aliza 'Aini; Nordin, Anis Nurashikin; Hashim, Uda (2013)
The accelerated growth of wireless communication system has increased the interest of research in CMOS integration in RF MEMS. A complete integrated silicon based resonator potentially eliminates lossy interfacing to on chip electronics. This paper presents the equivalent circuit modeling of a CMOS SAW resonator implemented in 0.35 μm CMOS technology. The periodic spacing of the IDTs based on the CMOS technology controls the resonance frequency of the resonator. Four different resonators at frequency range of 0.750 GHz to 1.125 GHz were simulated using MATLABTM based on theoretical equations. High quality factors and low insertion loss is crucial to optimize the performance of the SAW resonator. Crucial design parameters such as periodic spacing, number of reflectors, array of reflectivity and coupling coefficient are highlighted. The simulated results shows high quality factor in the order of thousands and low insertion loss, which is crucial to optimize the performance of the Al doped ZnO CMOS SAW resonator.